2007
DOI: 10.1111/j.1600-0854.2007.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Vacuolar Transport Receptors and Cargo Proteins in the Golgi Apparatus of Developing Arabidopsis Embryos

Abstract: Using immunogold electron microscopy, we have investigated the relative distribution of two types of vacuolar sorting receptors (VSR) and two different types of lumenal cargo proteins, which are potential ligands for these receptors in the secretory pathway of developing Arabidopsis embryos. Interestingly, both cargo proteins are deposited in the protein storage vacuole, which is the only vacuole present during the bent‐cotyledon stage of embryo development. Cruciferin and aleurain do not share the same patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 70 publications
10
91
1
Order By: Relevance
“…However, little is known about the trafficking of VSRs through the SYP61 compartment. VSR1 is thought to direct ntVSS cargo to the PVC in a clathrin-dependent pathway [43], although recent studies have expanded this view by showing that ctVSS cargo follows the same route [41,44,45]. Our proteomic analysis revealed the presence of several VSRs in SYP61 vesicles, including VSR4 (At2g14720), VSR3 (At2g14740) and VSR7 (At4g20110; Supplementary information, Tables S1 and S2), with localization studies showing clearly that VSR4-YFP was colocalized with SYP61-CFP in stably transformed plants ( Figure 2D-2F).…”
Section: Vsrs In the Syp61 Compartmentmentioning
confidence: 99%
“…However, little is known about the trafficking of VSRs through the SYP61 compartment. VSR1 is thought to direct ntVSS cargo to the PVC in a clathrin-dependent pathway [43], although recent studies have expanded this view by showing that ctVSS cargo follows the same route [41,44,45]. Our proteomic analysis revealed the presence of several VSRs in SYP61 vesicles, including VSR4 (At2g14720), VSR3 (At2g14740) and VSR7 (At4g20110; Supplementary information, Tables S1 and S2), with localization studies showing clearly that VSR4-YFP was colocalized with SYP61-CFP in stably transformed plants ( Figure 2D-2F).…”
Section: Vsrs In the Syp61 Compartmentmentioning
confidence: 99%
“…Analysis of ICF from the tno1 mutant demonstrated partial secretion of AALP, in common with mutants in the additional SYP41 complex components VPS45 and VTI12 (Sanmartín et al, 2007;Zouhar et al, 2009). AALP has dual vacuolar targeting signals and is a cargo for VSR1 (Hinz et al, 2007). Therefore, TNO1, AtVPS45, and VTI12 may cooperate in VSR1-mediated vacuolar trafficking via recycling of VSR1 from PVC to TGN.…”
Section: Phenotype Of the Tno1 Knockout Mutantmentioning
confidence: 99%
“…In the TGN, vacuolar proteins with sequencespecific vacuolar sorting determinants are thought to be recognized by vacuolar sorting receptors (VSRs; Kirsch et al, 1994;Ahmed et al, 2000;daSilva et al, 2005), although a recent report has suggested that recognition of cargo by VSRs may occur as early as the ER (Niemes et al, 2010). Storage proteins with C-terminal sorting sequences are also bound by VSRs or by a second putative sorting receptor, RMR1 (Jiang et al, 2000;Shimada et al, 2003a;Park et al, 2005Park et al, , 2007Hinz et al, 2007). After the receptors recognize their cargo, vacuolar proteins are transported to the prevacuolar compartment (PVC; Sanderfoot et al, 1998;Happel et al, 2004;Song et al, 2006) before transport on to the vacuole.…”
mentioning
confidence: 99%
“…In dicots such as legumes and Arabidopsis, MVBs receive seed storage proteins and their processing proteases from the Golgi and carry them to the PSVs (Hohl et al, 1996;Robinson et al, 1998;Robinson and Hinz, 1999;Hillmer et al, 2001;Jolliffe et al, 2005;Otegui et al, 2006;Hinz et al, 2007). In developing pumpkin seeds, the pro-11S globulin and pro-2S albumin precursors segregate from the ER to form the central core of precursor-accumulating (PAC) vesicles, bypassing the Golgi (Hara-Nishimura et al, 1985Fukasawa et al, 1988;Herman and Schmidt, 2004).…”
Section: Autophagy In Cereal Endosperm Cellsmentioning
confidence: 99%